Penentuan Umur Simpan Sirup Pala Menggunakan Metode ASLT (Accelerated Shelf Life Testing) Dengan Pendekatan Arrhenius - Fallen B. Sandana; Dekie Rawung; Maya Ludong; Christine Mamuaja (COCOS, 2014)
ABSTRACTNutmeg syrup is one way to diversify products of nutmeg. IKM â€œSari Fruitâ€ is one of nutmeg syrup producers in North Sulawesi, especially in the District Sitaro. However, nutmeg syrup in the market has not specified expiration date. One method that can be used to determining the shelf life of food product is ASLT (Accelerated Shelf Life Testing). This research aims to determine the shelf life of nutmeg syrup production IKM "Sari Fruit" Sitaro using ASLT (Accelerated Shelf Life Testing) with the Arrhenius approach. The benefit of this research is to give information and advice to the industry of nutmeg syrup to determine the shelf life of the product before it is marketed. In this research, nutmeg syrup stored at 30 Â° C, 35 Â° C and 40 Â° C for 4 weeks. The parameters used to analyze the decline in the quality of nutmeg syrup are pH, sugar content, viscosity, total yeast and organoleptic tests. The results showed that the shelf life calculations are based on the pH because it has the smallest activation energy, ie 4,025.66 cal / mol. Shelf life of nutmeg syrup at room temperature storage (27 Â° C) was 13.6 weeks.Keywords : Nutmeg syrup, shelf life, ASLT, Arrhenius